Modernisasi Shorf Dalam Al Bahtsu Ashorfi Fid Dirosah Lugowiyah ‘Arabiyah Haditsah Karya Nasrin Abdullah Syanuf ‘Alwani - Eka Safitri; Ihsan Sa'dudin (Indonesian Journal of Arabic Studies, 2019)
Morphology (shorof) can not be separated from the study of Arabic language. As the determination of Arabic into an international language, the study of classical Arabic language needs to be developed more broadly and integrated with modern linguistics so that Arabic can be learned easily by all people in this modern era. Like Nasrin Abdullah Syanuf's study â€˜Alwani in Albahtsu Ashorfi Fid Dirosah Lugowiyahâ€˜ Arabiyah Hadithah regarding modern Arabic morphology (modern shorof) discovered several new rules, among which there is no term Ø§Ù„ØªÙ‚Ø§Ø¡ Ø³Ø§ÙƒÙ†ÙŠÙ†; Long Meaning and Origin of Words; Influence of Intonation (Ø§Ù„Ù†Ø¨Ø±) in Arabic Morphology; Substitution of Hamzah with Harkat Panjang; Location of Hamzah at the end of the word after Alif Zaidah; Prular Form ÙØ¹Ø§Ø¦Ù„ ; and taqsir.